2018
DOI: 10.7759/cureus.3419
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma of the Foot: A Case Report

Abstract: Leiomyomas are benign tumors of smooth muscle origin. They are most commonly found in the uterus, but cutaneous leiomyomas may be occasionally present in the extremities and cause pain secondary to mass effect. Few studies have reported leiomyoma of the foot, and leiomyoma of the heel is particularly rare. We present a case of a 41-year-old female who presented to our clinic for a tender nodule on the posterior aspect of her right heel. The tumor was surgically excised and biopsied revealing cutaneous leiomyom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Upon reviewing the literature, it was found that there were not many published cases of foot leiomyoma. Examples include the case series of Szolomayer et al, which included eight patients with excised leiomyomas of the ankle, plantar foot, and hallux [ 5 ], and Jalgaonkar et al, on the other hand, which described a case of a leiomyoma in the plantar side of the forefoot that was primarily identified as a fibroma [ 6 ]; Stock et al's case of leiomyoma in the dorsolateral aspect of the foot of a 50-year-old male patient, where it was a slowly growing mass over 10 years before undergoing core needle biopsy without excision [ 7 ]; Savage et al's 2019 report of a patient with a plantar arch leiomyoma [ 8 ]; and Buddemeyer et al's 2018 case report detailing the discovery of a 41-year-old female patient's cutaneous leiomyoma in the heel [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upon reviewing the literature, it was found that there were not many published cases of foot leiomyoma. Examples include the case series of Szolomayer et al, which included eight patients with excised leiomyomas of the ankle, plantar foot, and hallux [ 5 ], and Jalgaonkar et al, on the other hand, which described a case of a leiomyoma in the plantar side of the forefoot that was primarily identified as a fibroma [ 6 ]; Stock et al's case of leiomyoma in the dorsolateral aspect of the foot of a 50-year-old male patient, where it was a slowly growing mass over 10 years before undergoing core needle biopsy without excision [ 7 ]; Savage et al's 2019 report of a patient with a plantar arch leiomyoma [ 8 ]; and Buddemeyer et al's 2018 case report detailing the discovery of a 41-year-old female patient's cutaneous leiomyoma in the heel [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst piloleiomyoma have a greater affiliation, all subtypes of cutaneous leiomyoma may be present with HLRCC. Identification of cutaneous leiomyomas should raise clinical suspicion for HLRCC and genetic testing considered if clinically indicated (12). Although inconsistent, a few cases of angioleiomyoma of extremities have been found to harbor cytogenetic abnormalities (21).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous foot and ankle locations have been reported in the literature following excisional biopsy. These include; tarsal tunnel (3), subfascia of lower leg (5), second intermetatarsal space (2), dorsal medial midfoot (6), lateral malleolus (7), first intermetatarsal space (8,9) plantar proximal webspace (10), posterior heel (11,12,13), inferior heel (1,14), hallux (15), plantar aspect of the second intermetatarsal region (15), third digit (15) and plantar medial arch (16).…”
Section: Introductionmentioning
confidence: 99%
“…80 %) an den Extremitäten vorkommen. Bevorzugt in der Knöchelregion, weniger an den Armen (im Verhältnis 3:1) [1,2]. Selten sind sie akral lokalisiert, meist an den Fingern [1], weitere Lokalisationen sind Kopf und oberer Stamm.…”
Section: Kommentarunclassified